Delanzomib, a Novel Proteasome Inhibitor, Combined With Adalimumab Drastically Ameliorates Collagen-Induced Arthritis in Rats by Improving and Prolonging the Anti-TNF-α Effect of Adalimumab - Wang, Lei; Liu, Lixiong; Hong, Xiaoping; Liu, Dongzhou; Cheng, Zeneng (Frontiers in Pharmacology, 2021)
Delanzomib is a novel proteasome inhibitor initially developed for treating multiple myeloma. It was found to inhibit the expression of tumor necrosis factor alpha (TNF-α). This study aimed to investigate the ameliorating effect of delanzomib on collagen-induced arthritis (CIA) and to explore the pharmacodynamics and pharmacokinetics (PK) interactions between delanzomib and adalimumab. Rats with CIA were randomly assigned to receive the treatment with delanzomib, adalimumab, delanzomib combined with adalimumab, or placebo. Visual inspection and biochemical examinations including TNF-α, interleukin 6, and C-reactive protein were performed to assess arthritis severity during the treatment. The adalimumab concentration in rats was determined to evaluate the PK interaction between delanzomib and adalimumab. Also, the levels of neonatal Fc receptor (FcRn) and FcRn mRNA were measured to explore the role of FcRn in the PK interaction between delanzomib and adalimumab. As a result, delanzomib combined with adalimumab exhibited stronger anti-arthritis activity than a single drug because both drugs synergistically reduced TNF-α level in vivo. Delanzomib also suppressed adalimumab elimination in rats by increasing the level of FcRn. The slower elimination of adalimumab in rats further prolonged the anti-TNF-α effect of adalimumab. Moreover, FcRn level was increased by delanzomib via suppressing FcRn degradation rather than promoting FcRn production. In conclusion, delanzomib combined with adalimumab may be a potential therapeutic approach for treating rheumatic arthritis. The initial finding that the PK interaction occurred between delanzomib and adalimumab may have clinical relevance for patients who simultaneously take proteasome inhibitors and anti-TNF-α therapeutic proteins.